2021
DOI: 10.1111/jonm.13265
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and cognitive emotion regulation strategies in Chinese nurses during the COVID‐19 outbreak

Abstract: Aims To explore the association between cognitive emotion regulation strategies and anxiety and depression among nurses during the COVID‐19 outbreak. Background Nurses play a vital role in responding to the COVID‐19 outbreak, but many of them suffer from psychological problems due to the excessive workload and stress. Understanding the correlation between cognitive emotion regulation strategies and anxiety and depression will promote targeted psychosocial interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 41 publications
3
46
0
1
Order By: Relevance
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 27 , 29 33 , 35 , 36 , 38 41 , 45 52 , 56 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 117 , 120 , 123 , 124 , 127 , 129 133 , 137 , 138 , 140 , 141 , 143 146 , 149 , 151 154 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…About two thirds (n = 98) of the studies reported the data on depression [ 8 , 23 27 , 29 33 , 35 , 36 , 38 41 , 45 52 , 56 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 , 89 , 91 , 92 , 94 , 95 , 97 , 99 , 100 , 103 , 104 , 106 – 108 , 111 , 113 , 115 117 , 120 , 123 , 124 , 127 , 129 133 , 137 , 138 , 140 , 141 , 143 146 , 149 , 151 154 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 117 out of 148 studies described the anxiety data in terms of frequency or percentage [ 8 , 10 , 11 , 24 27 , 30 33 , 35 42 , 45 56 , 58 60 , 62 65 , 67 69 , 71 76 , 78 82 , 84 , 86 , 88 95 , 99 , 100 , 103 114 , 116 118 , 120 , 122 135 , 137 141 , 143 145 , 149 , 151 154 , 156 165 ]. Tools that were used to screen for anxiety were Depression-Anxiety-Stress Scale-21 (DASS-21), 2-item and 7-item Generalized Anxiety Disorder (GAD-2& GAD-7), Hospital Anxiety and Depression Scale 14 items (HADS), Self-Rating Anxiety Scale (SAS), Hamilton Anxiety Scale (HAMA), Patient Health Questionnaire-4 (PHQ-4), Coronavirus Anxiety Scale (CAS), Chinese Classification and the Diagnose Criterion of Mental Disorder (CCMD-3), State and Trait Anxiety Inventory (STAI), Dispositional cancer worry scale, Symptom Checklist 90, and Beck Anxiety Scales (BAS).…”
Section: Resultsmentioning
confidence: 99%
“…We also suggest some of the measures that should be present on each level to mitigate the impact of trauma. For example, some of the individual-level protective factors include emotional and cognitive preparedness to face a natural or man-made disaster (Gabriel et al, 2007 ; Roudini et al, 2017 ), absence of pre-existing trauma and psychiatric history (Alvarez and Hunt, 2005 ; Esterwood and Saeed, 2020 ), good emotional regulation skills (Restubog et al, 2020 ; Wang et al, 2021 ), and sense of control during and after the disaster (Reich, 2006 ). At collective and societal levels, examples of protective factors include social support (Ehring et al, 2011 ; Huang et al, 2013 ; Pietrzak et al, 2014 ), community-level preparedness training (Morrissey and Reser, 2003 ), receiving post-disaster professional support (Tak et al, 2007 ; Brooks et al, 2016 ) and using social media as a source of information and psychological “first aid” (Finch et al, 2016 ; Yang et al, 2019 ).…”
mentioning
confidence: 99%
“…The impact of the Covid-19 pandemic has caused many losses such as physical health problems, economic inequality, social inequality and mental disorders (Wang et al 2020). Mental disorders that occurred during the Covid-19 pandemic were anxiety, fear, stress, depression, panic, sadness, frustration, anger, and denial (Huang et al 2020).…”
Section: Coronavirus Disease 2019 (Covid-19) Is An Infectious Disease Caused By Severementioning
confidence: 99%